MECHANISMS OF EDUCATIONAL STUDY OF STUDENTS ON THE BASIS OF MODERN PEDAGOGICAL TECHNOLOGIES - Tangirov Eldor Sayfullayevich (Journals Park Publishing, 2022)
In the article, based on a theoretical analysis of existing studies, studying the practice of organizing the work of the university, their own experience of working with students, the issue of the formation of personal tolerance is considered. The conceptual apparatus of the study is defined, problems associated with the multiculturalism of the student audience are identified, psychological and pedagogical approaches are proposed. conditions conducive to the effectiveness of the development of a tolerant personality.
Keywords: tolerance; multicultural environment; tolerance formation